Relationship between parental income and financial literacy level among students - Nur Yuhainis Ab Wahab; Crister Kujat; Norlaile Salleh Hudin (International Journal of Evaluation and Research in Education (IJERE), 2024)
Financial literacy has become an important element in improving the quality of individual, familial, societal, and national well-being. This study aims to find the relationship between parental income and financial literacy level among students at Universiti Pendidikan Sultan Idris. The research employed a quantitative method using a closed-ended questionnaire to collect the data for the analysis. The research sample was selected using a stratified sampling technique and simple random sampling that consists of 366 undergraduate education students. The result indicates that parental income has a weak and significant positive relationship with financial literacy levels among students. Based on the regression analysis, the father’s income explains about 2.76% of the variance in financial literacy, while the mother’s income explains 10.8% of the variance in financial literacy. The results of this study show that parental income has a relationship with student’s financial literacy level. This finding of this study will help to understand more about the factor that can affect financial literacy.